Consistency of motor actions as a factor of comprehensive development of a dance couple at the stage of initial training - N.D. Murzin (Theory and Practice of Physical Culture, 2023)
Ballroom dancing is a complex coordination sport, one of the main components and characteristics of which is the performance of a dance duet by two partners. The issue of motor consistency in a dance couple is relevant for research, especially among young dancers, since they have little experience in social interaction and dance practice to find motor compromises and work out their own consistency.